À propos des déficits gouvernementaux - Landry, Jean-Luc (Assurances, 1986)
In his article, the author deplores the ever-increasing budgetary deficits of our governments and concludes that: "Restoring financial equilibrium will, no doubt, require a revamping of our government social programmes and an in-depth revision of our tax system; but, it seems preferable to consider such changes now rather than waiting to be forced to react to situations beyond our control".